Enterococcus faecium 1.15 Isolated from Bakasam Showed Milk Clotting Activity - Wendry Setiyadi Putranto; Kusmajadi Suradi; Hartati Chairunnisa; Apon Zaenal Mustopa; Puspo Edi Giriwono; Harsi Dewantari Kusumaningrum; Maggy Thenawidjaja Suhartono (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2017)
The Lactic Acid Bacteria with Milk Clotting Activity (MCA) were isolated from Bakasam, an Indonesian traditional fermented meat. The isolate screening was carried out using modified method of Skim Milk Agar and Milk Clotting Activity Test, and the isolate was then identified using 16S rRNA. We found 4 isolates that showed MCA of 18-20 SU/ml. Identification using 16S rRNA indicated that the isolate ALG.1.15 was 99% (FR3-F primer) and 99% (FR3-R primer) identic with Enterococcus faecium. The isolate potentially produced renin-like protease to subtitute renin from veal.